1984
DOI: 10.1002/pssb.2221220160
|View full text |Cite
|
Sign up to set email alerts
|

The Variation of Light Transmission of Heavily Doped Ruby at Magnetic Resonance

Abstract: 08, o at microwave pumping. The E P R transitions H(T)-a r e shown 1 ) 420029 Kazan, USSR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Numerous studies have reported on the characteristics of PL from ruby, highlighting not only the R line but also additional PL peaks. [25][26][27][28][29][30][31][32][33][34][35] Shorter wavelength vibronic emissions at λ = 670 nm, paired Cr 3+ ion emissions at λ = 707 and 715 nm (N 1 and N 2 lines), and cluster emissions at λ = 770 nm have been observed, particularly in heavily Cr-doped rubies. [29][30][31][32][33][34][35] These additional PL peaks, broader than the narrow R line peak, significantly contribute to the integrated intensity of the PL peak area and the brightness of the PL image.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported on the characteristics of PL from ruby, highlighting not only the R line but also additional PL peaks. [25][26][27][28][29][30][31][32][33][34][35] Shorter wavelength vibronic emissions at λ = 670 nm, paired Cr 3+ ion emissions at λ = 707 and 715 nm (N 1 and N 2 lines), and cluster emissions at λ = 770 nm have been observed, particularly in heavily Cr-doped rubies. [29][30][31][32][33][34][35] These additional PL peaks, broader than the narrow R line peak, significantly contribute to the integrated intensity of the PL peak area and the brightness of the PL image.…”
mentioning
confidence: 99%
“…[25][26][27][28][29][30][31][32][33][34][35] Shorter wavelength vibronic emissions at λ = 670 nm, paired Cr 3+ ion emissions at λ = 707 and 715 nm (N 1 and N 2 lines), and cluster emissions at λ = 770 nm have been observed, particularly in heavily Cr-doped rubies. [29][30][31][32][33][34][35] These additional PL peaks, broader than the narrow R line peak, significantly contribute to the integrated intensity of the PL peak area and the brightness of the PL image. Therefore, characterizing these additional PL peaks is essential for 2-D fluorescence thermometry applications based on PL imaging from ruby.…”
mentioning
confidence: 99%